The effect of cooling method on damping capacity of Fe-16Cr-2.5Mo alloy. (March 2020) - Zhang, C; Guo, J B; Wang, C; Hasi, G W; Man, P; Guo, P F; Lin, G Q
Abstract: Damping capacity and magnetic domain structure of Fe-16Cr-2.5Mo alloy at different cooling rates have been investigated in this paper. DMA (Dynamic Mechanical Analyzer) was used to test the damping capacity. MFM (Magnetic Force Microscope) was used to observe the magnetic domain structures. The results indicated that furnace cooled alloy exhibited significantly higher damping capacity than water cooled alloy. For water cooled alloy, higher internal stress resulted in labyrinth domains' formation and pinned the domain walls from moving, so the damping capacity was poor. However in the furnace cooled alloy, lamellar domains with larger size were responsible for higher damping capacity. In addition, higher initial permeability could be obtained to favor the movement of domain walls and contributed to higher damping capacity, due to the decrease of magnetocrystalline anisotropy.